Notas sobre o pensamento decolonial e os estudos da comunicação - Amaral, Muriel Emídio Pessoa do (Revista Extraprensa, 2021)
This article presents, using a bibliographic review, the contributions of decolonial thought in the field of human and social sciences as a new epistemological and political movement. Based on contributions from authors who dialogue with this proposal, the text also intends to interface with communications studies as a decolonial proposal in epistemological points and in political actions of public recognition of marginalized groups, opening other discussions in the field.